Influence of physical activity and diet on stress and anxiety in higher education - Benavides-Sánchez, María José; Ubago-Jiménez, José Luis; Melguizo-Ibáñez, Eduardo; Alonso-Vargas, José Manuel (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Anxiety, physical inactivity, as well as poor adherence to a good diet are some of the most frequent problems among the university population. This may be mainly due to the preoccupation with studies, exams and all the work assignments, ending in little time for culinary and physical activity. All of this leads to an increase in pathologies such as stress and anxiety, which causes students to create bad habits. The aim of this study was to relate stress and anxiety levels, as well as physical activity and adherence to the Mediterranean diet in a sample of university students. The focus is therefore on the differences between gender and academic performance. For this purpose, a cross-sectional, descriptive, comparative, descriptive design study was used, with a sample of 272 university participants who completed the PREDIMED test, the Beck anxiety inventory and an Ad Hoc sociodemographic questionnaire. The main results obtained are that the female sex suffers a higher rate of anxiety than the opposite sex. In addition, it is important to highlight that people who practice more physical activity have lower levels of anxiety, obtaining that 8 out of 10 students who practice physical activity have lower levels of anxiety.